Widyowati, Dyah Penyelarasan Kurikulum Pendidikan Vokasi: Study Kasus SMKN 10, SMK Adhikawacana Surabaya dan politeknik NSC Surabaya (Nsc Press, 2015)
Education is not currently generating a lot of labor that is ready for the job market needs in an era of globalization. It is a challenge for governments and communities in building a proper education system so that there is no gap between education and the world of work. As one indicator of the necessity of learning curriculum that can meet the challenges of the business world in addition to the development of the technology industryandthe environment. The curriculum is a written document that is used as a reference in the implementation of the process of teaching and learning, therefore, the curriculum should be designed simple, easily understood and systematically. Responding to the challenges that exist, the vocational education is required as an effort that aims to create a society that quality, advanced, independent, and modern. Vocational education is an important part of the overall effort andearnest toenhancethe dignityofthe nation. This study analyzes the alignment of curriculum of vocational education (study cases in Surabaya SMK 10, SMK ADHIKAWACANA Surabaya and Surabaya Polytechnic NSC). Results found vocational curriculum has been aligned and complementary Polytechnic, visible all correspondence and archival course lies nestled in group C (specialization) precisely in C2 is a basic skills program, as well as for archival management courses and correspondence courses in business administration Polytechnic NSC Surabaya group of science subjects and skills (MKK). But the department of business administration curriculum emphasis there are also courses of expertise working groups (MKB)., With core courses are on the program expertise. While the competency of the level of vocational and Polytechnic are in accordance with KKNI.